Period Gene Expression in Four Neurons Is Sufficient for Rhythmic Activity of Drosophila melanogaster under Dim Light Conditions. - Rieger, D.; Wülbeck, C.; Rouyer, F.; Helfrich-Förster, C. (Journal of Biological Rhythms, 2009)
The clock gene expressing lateral neurons (LN) is crucial for Drosophila 's rhythmic locomotor activity under constant conditions. Among the LN, the PDF expressing small ventral lateral neurons (s-LN(v)) are thought to control the morning activity of the fly (M oscillators) and to drive rhythmic activity under constant darkness. In contrast, a 5th PDF-negative s-LN( v) and the dorsal lateral neurons (LN(d)) appeared to control the fly's evening activity (E oscillators) and to drive rhythmic activity under constant light. Here, the authors restricted period gene expression to 4 LN-the 5th s-LN(v) and 3 LN(d)- that are all thought to belong to the E oscillators and tested them in low light conditions. Interestingly, such flies showed rather normal bimodal activity patterns under light moonlight and constant moonlight conditions, except that the phase of M and E peaks was different. This suggests that these 4 neurons behave as ''M'' and ''E'' cells in these conditions. Indeed, they found by PER and TIM immunohistochemistry that 2 LN(d) advanced their phase upon moonlight as predicted for M oscillators, whereas the 5th s-LN(v) and 1 LN(d) delayed their activity upon moonlight as predicted for E oscillators. Their results suggest that the M or E characteristic of clock neurons is rather flexible. M and E oscillator function may not be restricted to certain anatomically defined groups of clock neurons but instead depends on the environmental conditions.